Pengaruh Konsentrasi Air Kelapa Pada Pembibitantanaman Buah Naga (Hylocereus costaricencis) - Fodhil, Muhamad; ', Armaini; ', Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objectives of this research to determine the effect of coconut water concentration on dragon fruit (Hylocereus costaricensis) nursery. This research was conducted at dragon fruit plantation of dragon fruit Tameran, Bengkalis, in August to December 2012. This experiment used Completely Randomized Design (CRD) which consisting of 5 treatments and 4 replications. The treatments were Coconut Water Concentration (P) as followed: P1: 0% (0 ml coconut water in 100 ml of water), P2: 25 % (25 ml coconut water in 75 ml of water), P3: 50% (50 ml coconut water in 50 ml of water), P4: 75% (75 ml coconut water in 50 ml of water), P5: 100% (100 ml coconut water in 0 ml of water). Parameters observed: those appearing shoot, shoot length, number of shoot, added root length, added number of roots, root volume, fresh and dry weight. Data were analyzed statistically using analysis of variance (ANOVA) and further tested using Duncan New Multiple Range Test level 5%. The research suggested that 50% concentration coconut water was the best for growth added root length, added number of roots, root volume, fresh and dry weight. Keywords : Dragon fruit cutting, coconut water and growth.